Analysis of influencing factors of self-care self-efficacy among patients with digestive tract tumors (消化道肿瘤患者自我管理效能感的影响因素分析) - SHI Linlin (石琳琳); ZHANG Jinlan (张进兰); SHEN Pan (沈盼); ZHU Yalin (朱雅麟); DAI Cui (戴翠); CHAI Shouxia (柴守霞) (中西医结合护理)
Objective To investigate the status quo of self-care self-efficacy among patients with digestive tract cancer, and to explore its influencing factors, in order to provide a basis for making self-management programs for patients with digestive tract cancer. Methods A total of 443 patients with digestive tract tumors admitted to three Grade-A hospitals in Hubei Province from October 2021 to September 2022 were selected as subjects. Convenience sampling method was used to investigate the Chinese version of Strategies Used by People to Promote Health(SUPPH), Social Support Rate Scale(SSRS) and Medical Coping Modes Questionnaire(MCMQ). Results The SUPPH score was (75. 91±15. 64). Gender, place of residence, family per capita monthly income, children, social support and coping style were the main factors affecting the self-management efficacy of patients with digestive tract tumors (P＜0. 05). Conclusion The self-management efficacy of patients with digestive tract tumors is at a medium to low level. Higher level of social support is associated with stronger self-management efficacy of patients. Positive coping style is helpful to improve the self-management efficacy of patients. (目的 了解消化道肿瘤患者自我管理效能感水平现状, 探索其影响因素, 以期为消化道肿瘤患者针对性制定自我管理项目内容提供依据。方法 选取2021年10月—2022年9月湖北省三家三甲医院收治的443例消化道肿瘤患者作为研究对象, 采用便利抽样法, 使用中文版癌症自我管理效能感(SUPPH)、社会支持量表(SSRS)和医学应对方式问卷(MCMQ)进行调查。结果 患者的SUPPH得分为(75. 91±15. 64)分; 性别、居住地、家庭人均月收入、子女情况、社会支持及应对方式是影响消化道肿瘤患者自我管理效能感的主要因素(P<0. 05)。结论 消化道肿瘤患者自我管理效能感处于中低水平。患者的社会支持水平越高, 其自我管理效能感越强, 积极应对方式有助于提升其自我管理效能感。)